1984
DOI: 10.1113/jphysiol.1984.sp015293
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth and ectopic synapse formation induced by muscle damage in the frog.

Abstract: The effect of muscle damage on nerve growth and ectopic synapse formation in the frog was investigated by bisecting the cutaneus pectoris (c.p.) muscle following implantation of the hypoglossal nerve. Axons from the stump of the implanted nerve grew considerable distances towards the ends of the cut muscle fibres where they formed synapses. In some preparations, c.p. was only partially cut and in these muscles axonal growth from the implanted nerve occurred across intact fibres to reach the cut ends in the dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In experiments similar to the present ones, the formation and release of a diffusible factor from the damaged frog muscle fibres has been suggested by Sayers & Tonge (1984). They observed that injury to muscle stimulates nerve growth and formation of ectopic synapses by an implanted foreign nerve.…”
Section: Source Of the Stimulu8 For Functional Polyneuronal Innervationsupporting
confidence: 76%
See 1 more Smart Citation
“…In experiments similar to the present ones, the formation and release of a diffusible factor from the damaged frog muscle fibres has been suggested by Sayers & Tonge (1984). They observed that injury to muscle stimulates nerve growth and formation of ectopic synapses by an implanted foreign nerve.…”
Section: Source Of the Stimulu8 For Functional Polyneuronal Innervationsupporting
confidence: 76%
“…It was of interest to investigate whether local muscle injury also alters the pattern of frog muscle innervation since it modifies muscle activity, induces extra-junctional sensitivity to ACh and makes muscle fibres receptive to additional foreign innervation (Katz & Miledi, 1961, 1964Miledi, 1963;Sayers & Tonge, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Since junctional folds are absent in extrasynaptic regions, examining neuromuscular junctions induced at previously endplate-free regions may provide further insights into the differentiation of active zones. Ectopic neuromuscular junctions, complete with nerve terminals and Schwann cells, can be induced de novo in frogs by excising the original endplate sites and implanting the nerve to an endplate-free region of the muscle (Miledi, 1962(Miledi, , 1963Ding, 1982;Sayers and Tonge, 1984). Accumulation of ACh receptors and acetylcholinesterase, and the differentiation of new junctional folds (Korneliussen and Sommerschild, 1976;Lomo and Slater, 1980;Breitschmid and Brenner, 198 1;Weinberg et al, 198 1) are observed in ectopic junctions.…”
mentioning
confidence: 99%
“…Accumulation of ACh receptors and acetylcholinesterase, and the differentiation of new junctional folds (Korneliussen and Sommerschild, 1976;Lomo and Slater, 1980;Breitschmid and Brenner, 198 1;Weinberg et al, 198 1) are observed in ectopic junctions. Physiological studies have shown by the presence of spontaneous and evoked endplate potentials that ectopic junctions are functional (Miledi, 1962;Sommerschild, 198 1;Ding, 1982;Sayers and Tonge, 1984). Ding (1982) has shown that quanta1 contents at ectopic junctions are approximately 2.5 times larger than normal.…”
mentioning
confidence: 99%